Peran Pemerintah Desa di Bidang Pertanahan di Desa Pledo, Kecamatan Witihama, Kabupaten Flores Timur - Apriyanti P.A. Meo Ebang; Stephanie Perdana Ayu Lawalu; Frans Nyong (Universitas Kristen Indonesia Toraja, 2024)
Indonesia is known as agricultural country, where most of the citizen work and lives cannot be separated from land to meet their daily needs. Land is very valuable for the community because it is the place where people live and work to meet their daily needs, and also because of its high value having a land acts as a long term investment for the owner. However, in Indonesia land problem often arise as a result of land ownership disputes. The problem experienced by people in Pledo Village, Witihama District, East Flores Regency, caused by a situation where people usually claim ownership of a land which has been inherited from their ancestors, but without any legal ownership sertificate. This problem has occurred so often that it has disadvantaged all the activities of the community in Pledo Pledo Village.So the aim of this community service activity is to give information about the role of the local village government in mediating land conflicts and in the making of land ownership certificate.